2007
DOI: 10.1002/jclp.20353
|View full text |Cite
|
Sign up to set email alerts
|

Good grief and not‐so‐good grief: Countertransference in bereavement therapy

Abstract: This study examined the relationship between therapists' grief related to the death of a loved one and clients' perceptions of the process of bereavement therapy. Mail survey data were obtained from 69 client-therapist dyads. Results indicated that the extent to which therapists missed deceased loved ones was inversely related to client perceptions of therapist empathy, but not to client ratings of the alliance, session depth, or therapist credibility. Therapist acceptance of the death of a loved one was unrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
1
21
0
5
Order By: Relevance
“…Empathy scales were used in an effort to establish the discriminant validity of the Spanish-language WAI-S-P and WAI-S-T; however, the significant correlations of these two measures with the EUS-P and EUS-T respectively, were probably produced for the following reasons: (1) the bond and the empathy contain common elements such as respect between patient and therapist and a mutual understanding between them (Horvath 1981), (2) a high level of agreement about goals and tasks (Table 2) required the clinicians to have a high level of empathy, and (3) this high level of consensus lead the patients to perceive their therapists as empathic professionals. In any case, these findings are similar to those found in previous studies that used the Englishlanguage WAI-S-P and EUS-P (Fuertes et al 2006(Fuertes et al , 2007Hayes et al 2007;Kim et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…Empathy scales were used in an effort to establish the discriminant validity of the Spanish-language WAI-S-P and WAI-S-T; however, the significant correlations of these two measures with the EUS-P and EUS-T respectively, were probably produced for the following reasons: (1) the bond and the empathy contain common elements such as respect between patient and therapist and a mutual understanding between them (Horvath 1981), (2) a high level of agreement about goals and tasks (Table 2) required the clinicians to have a high level of empathy, and (3) this high level of consensus lead the patients to perceive their therapists as empathic professionals. In any case, these findings are similar to those found in previous studies that used the Englishlanguage WAI-S-P and EUS-P (Fuertes et al 2006(Fuertes et al , 2007Hayes et al 2007;Kim et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…The interviewees reported that they found some comfort in the structure of their work (Givelber & Simon, 1981) however, they also mentioned that their emotional state was unstable and at times it would interfere with providing therapy. This relates to the previously mentioned findings of how unresolved losses and issues may have a negative impact in the therapeutic process (Hayes et al, 2007;Rosenberg & Hayes, 2002).…”
Section: Therapists' Experiences Of the Death Of A Close Related Kinmentioning
confidence: 99%
“…Therapists' defences such as denial, omnipotence, narcissistic withdrawal and reaction formation against weakness (Bram, 1995;Chernin, 1976;Counselman & Alonso, 1993;Dewald, 1994;Halpert, 1982) may cause great harm to the neutrality, objectivity, empathy and general engagement with the client (Counselman & Alonso, 1993;Halpert, 1982). A therapist's unresolved losses may affect negatively the therapeutic process as any other unresolved issues (Hayes et al, 2007). From the above, it becomes evident that if therapists acknowledge and "work through" their loss of health and own mortality, then their therapeutic practice can develop and improve.…”
Section: Other Types Of Therapists' Personal Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that the preoccupied attachment style, usually associated with early childhood aversive experience, is signifi cantly correlated with high self-reported levels of empathy among master's level counselors (Trusty et al, 2005). A recent study of bereavement therapy even found that unresolved grief in the therapists -but not their overall grief experience -was related to higher ratings of empathy by their patients (Hayes et al, 2007).…”
mentioning
confidence: 98%